Day of the Dead in the USA : the migration and transformation of a cultural phenomenon - Marchi, Regina M., 1965- (Latinidad., 2022)
Examines how Day of the Dead celebrations among America's Latino communities have changed throughout history, discussing how the traditional celebration has been influenced by mass media, consumer culture, and globalization.